Efficacy and safety of ustekinumab treatment in adults with moderate-to-severe atopic dermatitis - Khattri, Saakshi (Exp Dermatol, 2016)
BACKGROUND: Atopic dermatitis (AD) is the most common inflammatory skin disease, but treatment options for moderate-to-severe disease are limited. Ustekinumab is an IL-12/IL-23p40 antagonist that suppresses Th1, Th17 and Th22 activation, commonly used for psoriasis patients. OBJECTIVE: We sought to assess efficacy and safety of ustekinumab in moderate-to-severe AD patients. METHODS: In this phase II, double-blind, placebo-controlled study, 33 patients with moderate-to-severe AD were randomly assigned to either ustekinumab (n=16) or placebo (n=17), with subsequent crossover at 16wks, and last dose at 32wks. Background therapy with mild topical steroids was allowed to promote retention. Study endpoints included clinical (SCORAD50) and biopsy-based measures of tissue structure and inflammation, using protein and gene expression studies. RESULTS: The ustekinumab group achieved higher SCORAD50 responses at 12wks, 16wks (the primary endpoint), and 20wks compared to placebo, but the difference between groups was not significant. The AD molecular profile/transcriptome showed early robust gene modulation, with sustained further improvements until 32wks in the initial ustekinumab-group. Distinct and more robust modulation of Th1, Th17 and Th22 but also Th2-related AD genes was seen after 4wks of ustekinumab treatment (i.e. MMP12, IL-22, IL-13, IFN-γ, elafin/PI3, CXCL1, CCL17; p<0.05). Epidermal responses (K16, terminal differentiation) showed faster (4wks) and long-term regulation (32wks) from baseline in the ustekinumab-group. No severe adverse events were observed. CONCLUSIONS: Ustekinumab had clear clinical and molecular effects, but clinical outcomes might have been obscured by a profound “placebo” effect, most likely due to background topical glucocorticosteroids and possibly insufficient dosing for AD.